Can the high intensity interval running in slope affect concurrently explosive strength performance? - Pereira Rocha, Fernanda; Meireles Santos, Tony; Oliveira-Silva, Iransé; Albernaz, Thiago; Querido Inacio, Pedro Augusto; Barsanulfo, Silvio Roberto; Coelho Silva, Adriano; Sales, Marcelo; Sardinha Leonardo, Patrícia; Lopes-Martins, Rodrigo Alvaro Brandão; de Conti Teixeira, Gustavo; Santos, Karllos Henrique; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Physical exercise programs are typically composed of activities directed to the development of different physical abilities, usually stimulated in the same session. Objective: The aim of the study was to determine the effect of one session of aerobic exercise at high intensity to 1% and 10% gradient on the height (HJump) and kinematics of the depth jump (PExc - eccentric, concentric phase PCon, and contact time – CT). Methods: Twenty-five moderately trained men (VO2Max 53.2 ± 4.3 mL.kg-1.min-1) attended five visits in the laboratory. Familiarity with the procedures in depth jump, VO2Max measures and their velocity associated (VVO2Max), and time to exhaustion performance (TLim) were performed at two initial visits. Results: On the three subsequent visits, the volunteers were subjected to three maximum depth jumps before and 10 min after the following conditions: (1) running intervals at high intensity of 10% gradient (R10%), (2) at 1% gradient (R1%), and control condition (CON). The order of conditions was determined randomly. A running condition did not induce significant changes from HJump (R1% 1.1% vs 1.0% R10%) when expressed as percentage difference from the CON condition. The PExc, PCon, and CT also did not change after running sessions (P> 0.05). None of the intervals running strategies were able to generate significant change in height and kinematics of the vertical depth jump. Conclusion: The prescription of the running at VVO2Max in 1% or 10% gradient does not seem to lead to concurrent effect, is suggested to ensure the concomitant development of maximal aerobic power and explosive strength.